+0  
 
0
212
2
avatar+75 

If f(x)=x10+2x9-2x8-2x7+x6+3x2+6x+1, then what is f(√(2-1))

 Oct 16, 2018
 #1
avatar+8069 
+1

\(If\ f(x)=x^{10}+2x^9-2x^8-2x^7+x^6+3x^2+6x+1\ ,\) 

                                                                        \(then\ what\ is\ f(\sqrt{2-1}\ )\)

 

\(f(\sqrt{2-1})=f(\sqrt1\ )=1\)

 

laugh  !

 Oct 16, 2018
edited by asinus  Oct 16, 2018
 #2
avatar+316 
+2

Why f(1) = 1? 

\(f(\sqrt{2-1}) = f(\sqrt{1}) = f(1) \)

so \(f(1)= 1^10 + 2(1)^9 - 2(1)^8 - 2(1)^7 + 1^6 + 3(1)^2 + 6(1) + 1 = 1 + 2 - 2 - 2 + 1 + 3 + 6 + 1 = 3 + 6 + 1 = 10 \)

so \(f(1) = 10 \) not 1,where im wrong?

Thanks! 

Dimitristhym  Oct 16, 2018
edited by Dimitristhym  Oct 16, 2018

7 Online Users

avatar